IFPRI Malawi monthly maize market report, January 2025 - International Food Policy Research Institute; Banda, Chimwemwe (International Food Policy Research Institute, 2025)
Highlights  Retail prices of maize increased by 21 percent in January.  Maize prices were lowest in the Northern region, where informal imports from Tanzania and northern Zambia enter the country, and increased southward.  Some maize was exported to southern Zambia, but high prices in southern Malawi attracted imports from Mozambique.  At the market exchange rate, retail prices of maize in Malawi were similar to those in Zambia and lower than in Mozambique and Zimbabwe.